Complicated Hereditary Spastic Paraplegia Caused by SERAC1 Variants in a Chinese Family - Yan, Dandan; Chen, Shaopei; Cai, Fengying; Shu, Jianbo; Zhi, Xiufang; Zheng, Jie; Zhang, Chunhua; Li, Dong; Cai, Chunquan (Frontiers in Pediatrics, 2022)
Background SERAC1 biallelic variant usually causes MEGDEL syndrome, its clinical characteristics are the increased excretion of 3-methylglutaconic in the urine, muscle hypotonia, sensorineural deafness, and Leigh-like lesions on brain magnetic resonance imaging (MRI). In this study we presented a case from a Chinese family with metabolism disorder and dystonia because of SERAC1 variant, the clinical phenotypes of proband were different from MEGDEL syndrome which were previously reported, but were similar to juvenile-onset complicated hereditary spastic paraplegia. In this study, we aimed to confirm the relationship between SERAC1 variants and complicated hereditary spastic paraplegia. Methods MRI and laboratory testing were performed in this patient.Whole exome sequencing was performed to detect the candidate variants. Then the variants were verified by Sanger sequencing. Various software were used to predict the pathogenicity of novel variants. Results Brain MRI showed abnormalities of bilateral basal ganglia symmetrically, putamen hyperintensities in T2WI and FLAIR. The excretion 3-methylglutaconic acid was increased in laboratory testing by gas chromatography-mass spectrometry. The whole exome sequencing showed novel compound heterozygous variants, including a novel c.1495A>G (p.Met499Val) in exon 14 of SERAC1 gene inherited from her father, and a novel c.721_722delAG (p.Leu242fs) in exon 8 inherited from her mother. The prediction results of software showed that two variants were harmful. Conclusions This study showed a patient of complicated hereditary spastic paraplegia caused by SERAC1 variants. These findings expand the variant spectrum of SERAC1 gene and the phenotypic spectrum of SERAC1 deficiency. This study is helpful in counseling and prevention through prenatal diagnosis.